Pengaruh kebiasaan minum kopi terhadap konsentrasi belajar mahasiswa di tengah kemajuan digital - Rahmawati, Eni (Maliki Interdisciplinary Journal, 2026)
This study aims to examine the effect of coffee drinking habits on students’ concentration levels in a learning context increasingly influenced by advances in digital technology. Coffee, a caffeinated beverage, has long been known to have a stimulant effect that can potentially increase alertness and focus. However, in today’s digital age, distractions from gadgets and various online platforms pose new challenges to students’ concentration. The research method used was a quantitative survey, with a sample of active students at several universities, in particular. Data were collected using a questionnaire that measured the frequency of coffee consumption and concentration levels while studying. Statistical analysis was performed to examine the relationship between coffee drinking habits and concentration levels. The results showed a significant positive correlation between coffee consumption and increased concentration levels, although the degree of effect varied depending on the intensity of digital device use. This research provides important insights into the role of coffee as a contributing factor to academic success in the digital age and allows for judicious management of coffee consumption to maximize its benefits without causing negative effects. The implications of this study’s results can serve as a reference for students and educators in managing effective learning conditions in modern learning environments.